The Effectiveness of Nature Exploration Games in Sharpening Problem-Solving Skills - Nurhikmah; Ibnu Imam Al Ayyubi; Siti Fatinnah binti Ab Rahman (GENIUS: Journal of Elementary Pedagogy and Innovation Studies, 2025)
This study aims to examine the effectiveness of nature exploration games in honing problem-solving skills in early childhood at RA Al-Jazila Padalarang, West Bandung Regency, with the population consisting of all students at RA Al-Jazila. The sample included 20 students from classes B1, B2, and B3 as the experimental group, and 20 students from class B4 as the control group, selected through purposive sampling. This research adopts a quantitative approach using an experimental method and a quasi-experimental design with a non-equivalent control groups design. Data processing was conducted using SPSS version 26, and non-parametric statistical analysis was performed with the median test. The results show that although there was an increase in the average score in the experimental group, no significant difference was found between the experimental and control groups based on the statistical test. This indicates that nature exploration games did not have a significant impact on improving problem-solving skills in early childhood in this study. However, the study provides an important insight into the need for more structured and sustainable learning designs to achieve optimal results.